2006
DOI: 10.1111/j.1365-2826.2006.01455.x
|View full text |Cite
|
Sign up to set email alerts
|

Brief Treatment With the Glucocorticoid Receptor Antagonist Mifepristone Normalises the Corticosterone‐Induced Reduction of Adult Hippocampal Neurogenesis

Abstract: The glucocorticoid receptor antagonist mifepristone has been shown to rapidly and effectively ameliorate symptoms of psychotic major depression. To better understand its mechanism, we investigated mifepristone's cellular effects, and found that it rapidly reversed a chronic corticosterone-induced reduction of adult neurogenesis in rats. Unlike other antidepressants, mifepristone is particularly potent in a high corticosterone environment. These data indicate that similarly to its clinical efficacy, mifepriston… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
107
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 163 publications
(121 citation statements)
references
References 23 publications
11
107
0
2
Order By: Relevance
“…A large body of evidence has demonstrated that chronically high concentrations of glucocorticoids impair hippocampal neurogenesis, that is, the development of new neurons from stem cells in the dentate gyrus, by activating the glucocorticoid receptor (GR) (1)(2)(3)(4)(5)(6). However, the mechanisms by which GR activation reduces neurogenesis are not fully understood.…”
mentioning
confidence: 99%
“…A large body of evidence has demonstrated that chronically high concentrations of glucocorticoids impair hippocampal neurogenesis, that is, the development of new neurons from stem cells in the dentate gyrus, by activating the glucocorticoid receptor (GR) (1)(2)(3)(4)(5)(6). However, the mechanisms by which GR activation reduces neurogenesis are not fully understood.…”
mentioning
confidence: 99%
“…The antagonist prevented astrogliosis and excessive neuronal activation and reversed the suppressed markers for neurogenesis in the hippocampus induced by the diabetic state and associated high corticosterone [66,75]. Cognitive deficits observed at day 11 of diabetes were also ameliorated resulting in a performance even better than the untreated controls [75].…”
Section: Normalization Of Hippocampal Alterations During Diabetes Melmentioning
confidence: 97%
“…This ends with a fully functional neuron that is integrated into the preexisting hippocampal network [38]. The existence and number of true multipotent neural stem• cells and DCX-positive cell numbers after chronic stress or corticosterone treatment is normalized by four days of high dose treatment with the GR antagonist mifepristone, whereas application of the drug alone to control animals has no effect (see Mayer et al [66] and Oomen et al…”
Section: Adult Hippocampal Neurogenesismentioning
confidence: 99%
See 2 more Smart Citations